Study of Some Physical Properties of Sb2o3:In2o3 Ceramic Nano Composites for Modern Application - Abeer S. Alfayhan , Prof. Dr. Raheem G. Kadhim Hussein (International Journal of Advanced Science and Technology, 2020)
Thin films from Sb2O3:In2O3were prepared with different weights and then the membranes were prepared using a drop casting method with an annealing temperature (250C). Some structural properties of Scanning Electron Microscope SEM, EDX. SEM images depict the surface morphology of Sb2O3 nanocomposite before and after addition In2O3, EDX know the chemical compounds in the sample .and Atomic Force Microscopic AFM indicated an increase in grain size of Sb2o3with increased with changing In2o3doping. Also, the optical properties studies included recording the permeability and absorbance of the prepared membranes and the wavelength range(110-300)nm, and it showed that the permeability of pure sb2o3 has a high amount in the visible area and it has little absorbency. The study also included the calculation of the absorption coefficient(α),and the gap energy of direct electronic transmissions. It was found that the energy gap decreases with increasing distortion of In2O3from (3.806, 3.734, 3.634, 3. 384) ev doping ratios (1%,2%,3%,4%) respectively.